2018
DOI: 10.5935/1518-0557.20180045
|View full text |Cite
|
Sign up to set email alerts
|

Luteal phase ovarian stimulation for poor ovarian responders

Abstract: ObjectiveTo compare the clinical outcomes of follicular versus luteal phase ovarian stimulation in women with poor ovarian response (Bologna criteria) undergoing IVF.MethodsThis retrospective study investigated 446 patients submitted to 507 cycles in three groups. First, the two larger cohorts were examined: 154 patients treated with luteal phase ovarian stimulation (Group Lu); and 231 patients administered follicular phase ovarian stimulation (Group Fo). Then the clinical outcomes of 61 patients submitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 24 publications
1
47
0
4
Order By: Relevance
“…If normal COS is in progress, early luteinization and follicular atresia will occur after a premature LH surge 9 . However, in our case, fertilization and implantation occurred after the presumed spontaneous ovulation day, and follicular development was observed after this time.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…If normal COS is in progress, early luteinization and follicular atresia will occur after a premature LH surge 9 . However, in our case, fertilization and implantation occurred after the presumed spontaneous ovulation day, and follicular development was observed after this time.…”
Section: Discussionmentioning
confidence: 57%
“…A previous study reported that the outcome of luteal phase ovarian stimulation (LU) was higher than that for follicular phase ovarian stimulation (FO) regarding the total dosage of hMG, M2 rate, 9 number of oocytes collected, fertilization rate, and the number of day 3 embryos 10 . Additionally, a study that compared FO only to FO + LU reported that the FO + LU group had a higher number of retrieved oocytes, M2 rate, and 2 PN rate 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Even though gonadotropin-releasing hormone analogs can prevent the premature rise [28], the potential LH surge remains [29]. When follicle recruitment during the luteal phase is performed using luteal phase ovarian stimulation (LPOS) [30], LPOS did augment oocytes pick-up and the number of Day 3 embryos, but there was no difference in the pregnancy rate [31]. Again, LPOS, coupled with MOSI, could be another option for poor responders.…”
Section: Discussionmentioning
confidence: 99%
“…16 Establishment of efficient vitrification techniques at every stage of preimplantation embryo development 18,19 along with our enhanced understanding of the physiologic, biochemical, and molecular mechanisms underlying antral follicular wave dynamics [20][21][22] have permitted the first description of double stimulation (DS) in 2013 23 and a modified version of DS couples with preimplantation genetic testing for aneuploidy (PGT-A), named dual stimulation (DuoStim) in 2016, 24 followed by several studies from different centers. [25][26][27][28][29][30][31][32][33][34][35] The goal of this mini-review article is to cover the available evidence of DS/DuoStim in POR patients.…”
Section: Introductionmentioning
confidence: 99%